2017
DOI: 10.3762/bjoc.13.277
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic dearomatization of 4-aza-6-nitrobenzofuroxan by CH acids in the synthesis of pharmacology-oriented compounds

Abstract: 4-Aza-6-nitrobenzofuroxan (ANBF) reacts with 1,3-dicarbonyl compounds and other CH acids to give carbon-bonded 1,4-adducts – 1,4-dihydropyridines fused with furoxan ring. In the case of most acidic β-diketones, which exist mainly in the enol form in polar solvents, the reactions proceed in the absence of any added base emphasizing the highly electrophilic character of ANBF. The resulting compounds combine in one molecule NO-donor furoxan ring along with a pharmacologically important 1,4-dihydropyridine fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In 1 H NMR spectra of adducts 4, the signals corresponding to H(7) protons in the range of 5.0-5.5 ppm, as well as downfield signals of NH protons (9.8-10.4 ppm) and H(5) at 8.1 ppm, were observed as doublets with close coupling constants. This confirms the nucleophilic addition at position 7 and is consistent with the results obtained previously for other highly electrophilic azolopyridines [45,46,48].…”
Section: Nucleophilic Addition To 6-r-isoxaxolo[43-b]pyridinessupporting
confidence: 92%
See 3 more Smart Citations
“…In 1 H NMR spectra of adducts 4, the signals corresponding to H(7) protons in the range of 5.0-5.5 ppm, as well as downfield signals of NH protons (9.8-10.4 ppm) and H(5) at 8.1 ppm, were observed as doublets with close coupling constants. This confirms the nucleophilic addition at position 7 and is consistent with the results obtained previously for other highly electrophilic azolopyridines [45,46,48].…”
Section: Nucleophilic Addition To 6-r-isoxaxolo[43-b]pyridinessupporting
confidence: 92%
“…It was found that nitro derivatives 3a-d react with all ranges of used nucleophiles under mild conditions (MeCN, room temperature, base-free), forming 1,4-addition products, 4a-m, Scheme 3. As in the case of A [45], β-dicarbonyl compounds react with 3 in enolic form. The reaction rate was similar to that of superelectrophiles A and B [45,46] (Scheme 1), thus indicating the high electrophilicity of isoxazolo[4,3-b]pyridine system.…”
Section: Nucleophilic Addition To 6-r-isoxaxolo[43-b]pyridinesmentioning
confidence: 93%
See 2 more Smart Citations
“…In case of C-nucleophiles these adducts can be isolated. Earlier we reported on reactions of some azolo[b]pyridines with 1,3-dicarbonyl compounds [4][5][6]. In this work we studied the reactions of dinitrobenzoannulated heterocycles (thiadiazole, selenadiazole, pyridine) with anionic C-nucleophiles (mono-and diketones, nitroalkanes and related compounds).…”
Section: Introductionmentioning
confidence: 99%